2018
DOI: 10.1186/s12883-018-1055-y
|View full text |Cite
|
Sign up to set email alerts
|

Creutzfeldt-Jakob disease with Alzheimer pathology, presenting with status epilepticus following repeated partial seizures: a case report and literature review

Abstract: BackgroundCreutzfeldt-Jakob disease (CJD) is a fatal neurodegenerative disease. Common first symptoms are dementia, cerebellar ataxia, visual disturbance, and psychiatric symptoms. Seizure as the first symptom of CJD is a very rare finding.Case presentationWe experienced an elderly woman who presented initially with status epilepticus following repeated partial seizures in the course of Alzheimer disease (AD) dementia. Anti-convulsive therapy had no effect. Autopsy revealed definite CJD with AD pathology.Coclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
2
3
2
Order By: Relevance
“…The co‐occurrence of CJD hallmarks with AD‐related findings on the neuropathological study, as in our patient, despite being uncommon, has been previously reported [ 13 , 14 ]. Published data suggest that the coexistence of CJD and AD hallmarks could present in two different ways, on one hand as a regular AD case developing CJD findings in the late stages, or on the other hand as a CJD case that also develops pathological features of AD, without typical clinical findings of AD [ 13 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The co‐occurrence of CJD hallmarks with AD‐related findings on the neuropathological study, as in our patient, despite being uncommon, has been previously reported [ 13 , 14 ]. Published data suggest that the coexistence of CJD and AD hallmarks could present in two different ways, on one hand as a regular AD case developing CJD findings in the late stages, or on the other hand as a CJD case that also develops pathological features of AD, without typical clinical findings of AD [ 13 ].…”
Section: Discussionsupporting
confidence: 76%
“…Also, as in our case, the first MRI at presentation only showed mild generalised volume loss; nevertheless, in that case follow-up MRI was performed, presenting diffusion and FLAIR hyperintensity in basal ganglia and pulvinar bilaterally. Genetic study was negative, and The co-occurrence of CJD hallmarks with AD-related findings on the neuropathological study, as in our patient, despite being uncommon, has been previously reported [13,14]. Published data suggest that the coexistence of CJD and AD hallmarks could present in two different ways, on one hand as a regular AD case developing CJD findings in the late stages, or on the other hand as a CJD case that also develops pathological features of AD, without typical clinical findings of AD [13].…”
Section: Discussionsupporting
confidence: 74%
“…5 Nearly one third of cases of variant CJD initially present with depression, emotional lability, behavioral changes, loss of appetite, and insomnia. 7,8 In the case presented, rapid loss of ADLs and markedly worsening depression should have led to a broader differential diagnosis and expedited the patient's disposition and care. The differential diagnosis for rapidly progressive dementia includes, but is not limited to, heavy metal toxicity, thyroid disorders, autoimmune disorders, vasculitis, sarcoidosis, viral or bacterial encephalopathies, and vitamin deficiencies, as well as CJD.…”
Section: Resultsmentioning
confidence: 98%
“…6,10 While CJD will rarely be diagnosed in the ED, it is important to note the progressive decline presented in the HPI and to begin the appropriate medical evaluation. 6,8…”
Section: Resultsmentioning
confidence: 99%
“…Given the rapid deterioration in the patient's clinical status, visual complaints, presence of myoclonus, cerebrospinal fluid markers, and EEG findings, a diagnosis of sporadic Creutzfeldt-Jakob disease (CJD) was made. Recurrent bifrontal delta discharge was observed in continuous EEG recordings of patients with CJD reported in the literature 1,2 . A computed tomography (CT) scan of the brain taken one year later revealed a neurodegenerative process and significant cortical atrophy (Figure 3).…”
Section: A Case Of Sporadic Creutzfeldt-jakob Diseasementioning
confidence: 95%